The Prevalence of Effective Substance Use Prevention Curricula in the Nation’s High Schools - Ringwalt, Chris (2008)
Despite a substantial proportion of high school students who initiate substance use following middle school, the implementation of universal evidence-based prevention curricula appears to be scant. We report data collected in 2005 from 1392 school-district based drug prevention coordinators, from a national, representative study of school-based substance use prevention practices. Altogether, 10.3% of districts that included high school grades reported administering one of six such curricula that were then rated as effective by the Substance Abuse and Mental Health Services Administration’s National Registry of Effective Programs and Practices or Blueprints for Violence Prevention, and 5.7% reported that they used one of these curricula the most. Only 56.5% of the nation’s districts with high school grades administered any substance use prevention programming in at least one of their constituent high schools.